SYMBOLS OF THE DEATHLY HALLOWS IN J.K. ROWLINGâ€™S â€œHARRY POTTER AND THE DEATHLY HALLOWSâ€ - Nasta, Mardiyanah; Hasriani G., Hasriani G.; Asriati, Asriati (Universitas Pendidikan Indonesia, 2020)
This research aimed to describe what the Deathly Hallows symbolized in J.K. Rowlingâ€™s â€œHarry Potter and the Deathly Hallowsâ€. This was a qualitative content analysis with hermeneutic approach. The primary data was from the novel of Harry Potter and the Deathly Hallows. The results of this research were the Deathly Hallows symbolized the thirst of the greatest power which could make the owner immortal, but for Harry Potter they symbolized a test, which tested his mission to defeat Voldemort. The Hallows themselves consisted of three objects which were the Elder Wand, the Resurrection Stone, and the Invisibility Cloak. Each of the Hallows also symbolized different things. The Elder Wand symbolized a wizardâ€™s desire for power, the Resurrection Stone symbolized deep longing towards the loved one who had died, and the Invisibility Cloak symbolized protection.